Widely tunable sub-kHz linewidth Tm3+-doped single-frequency fiber laser. (1st November 2022) - Jiang, Kui; Yang, Changsheng; Zhao, Qilai; Gu, Quan; Li, Jialong; Jiang, Wanpeng; Deng, Chunlan; Peng, Yan; Zhou, Kaijun; Feng, Zhouming; Yang, Zhongmin; Xu, Shanhui
Abstract: Based on a fiber Fabry–Pérot tunable filter and a 3.0 m long unpumped gain fiber for forming dynamic grating, an in-band pumped tunable Tm 3+ -doped single-frequency fiber laser covering a wavelength tuning range from 1857.01 to 2020.17 nm and a tuning interval of <0.43 nm is demonstrated experimentally. Additionally, the laser linewidths of <500 Hz and the relative intensity noises of < −145 dB Hz −1 at frequencies over 1 MHz are obtained. To date, it is the broadest wavelength tuning range that has been reported in the 2 μ m region, which is highly competitive in atmospheric detection.